Disentangling Genuine Semantic Stroop Effects in Reading from Contingency Effects: On the Need for Two Neutral Baselines - Lorentz, Eric; McKibben, Tessa; Ekstrand, Chelsea; Gould, Layla; Anton, Kathryn; Borowsky, Ron (Frontiers in Psychology, 2016)
The automaticity of reading is often explored through the Stroop effect, whereby color-naming is affected by color words. Color associates (e.g., ‘sky’) also produce a Stroop effect, suggesting that automatic reading occurs through to the level of semantics, even when reading sub-lexically (e.g., the pseudohomophone ‘skigh’). However, several previous experiments have confounded congruency with contingency learning, whereby faster responding occurs for more frequent stimuli. Contingency effects reflect a higher frequency-pairing of the word with a font color in the congruent condition than in the incongruent condition due to the limited set of congruent pairings. To determine the extent to which the Stroop effect can be attributed to contingency learning of font colors paired with lexical (word-level) and sub-lexical (phonetically decoded) letter strings, as well as assess facilitation and interference relative to contingency effects, we developed two neutral baselines: each one matched on pair-frequency for congruent and incongruent color words. In Experiments 1 and 3, color words (e.g., ‘blue’) and their pseudohomophones (e.g., ‘bloo’) produced significant facilitation and interference relative to neutral baselines, regardless of whether the onset (i.e., first phoneme) was matched to the color words. Color associates (e.g., ‘ocean’) and their pseudohomophones (e.g., ‘oshin’), however, showed no significant facilitation or interference relative to onset matched neutral baselines (Experiment 2). When onsets were unmatched, color associate words produced consistent facilitation on RT (e.g., ‘ocean’ vs. ‘dozen’), but pseudohomophones (e.g., ‘oshin’ vs. ‘duhzen’) failed to produce facilitation or interference. Our findings suggest that the Stroop effects for color and associated stimuli are sensitive to the type of neutral baseline used, as well as stimulus type (word vs. pseudohomophone). In general, contingency learning plays a large role when repeating congruent items more than incongruent items, but appropriate pair-frequency matched neutral baselines allow for the assessment of genuine facilitation and interference. Using such baselines, we found reading processes proceed to a semantic level for familiar words, but not pseudohomophones (i.e., phonetic decoding). Such assessment is critical for separating the effects of genuine congruency from contingency during automatic word reading in the Stroop task, and when used with color associates, isolates the semantic contribution.